A taxonomic revision of the genus Apostichopus (Holothuroidea: Stichopodidae) from Japan - Woo, Sau Pinn; Ogawa, Akito; Tan, Shau Hwai; Yasin, Zulfigar; Kajihara, Hiroshi; Fujita, Toshihiko (Zootaxa, 2017)
Complete redescriptions of sea cucumbers in the genus Apostichopus Liao, 1980 are provided using the type specimens and specimens deposited in the National Museum of Nature and Science, Tsukuba, Japan. The genus consists of A. armatus (Selenka, 1867) and A. japonicus (Selenka, 1867), which can be distinguished by some spicules in the dorsal body wall; the rim of reduced table spicules in A. armatus is spinous, while that in A. japonicus is smooth. Spicules from the tentacles, papillae, tube feet, and cloaca are similar for both species.